Institutions and Economics of Water Scarcity and Droughts - Berbel, Julio; Montilla-López, Nazaret M.; Giannoccaro, Giacomo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue opens a new field of research in certain emerging innovative instruments, because it provides an in-depth revision of the main aspects of institutions and instruments available for the management and governance of droughts and water scarcity. The key aspects that institutions may tackle not only include the increasing water scarcity in many regions around the world but also the increasing frequency and impact of droughts on economic and natural systems. Some of the included papers analyze critical issues, such as the state and future trends of water markets; the estimation of transaction costs when dealing with drought management; and the use of new instruments, such as insurance and water-rights entitlements, which include water security, water-pricing effects on the whole basin level, and intra- and inter-sectorial re-allocation. The important issues regarding non-conventional water supply and the governance of the new resources also feature as the focus of some of the contributions.